Net impact of COVID-19 on REIT returns - Yongpei Cai; Kuan Xu (Journal of Risk and Financial Management, 2022)
Using an extended Fama-French model for REIT returns, we examine how the net impact of the COVID-19 pandemic differs from that of recessions. We find that, as anticipated, recessions have a negative net impact on office and residential REIT returns but that the COVID-19 pandemic has a positive net influence on industrial REIT returns because of e-commerce and the demand for storage, distribution, and shipping. Contrary to what we anticipated, there are no negative net effects of the COVID-19 pandemic on office and residential REIT returns, perhaps caused by both existing office and residential leases, the percentage rent clause for commercial properties, and the grace period for residential properties during the COVID-19 pandemic. In contrast to moving solely during recessions and the COVID-19 pandemic, we find that retail REIT returns fluctuate along with ongoing macro/asset-pricing conditions throughout the boom and bust cycle.
Keywords: 650; COVID-19; portfolio management; real estate investment trusts